Patent and trade disparities in developing countries - Ragavan, Srividhya (New York ; Oxford : Oxford University Press, 2012)
In this work, Srividhya Ragavan examines the interaction between trade and intellectual property regimes (using the patent regime in India as the focal point) in an integrated developmental framework to determine how sustainable economic growth can be achieved in developing countries.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: Patent laws and legislation -- Developing countries; Foreign trade regulation -- Developing countries